2022
DOI: 10.1101/2022.06.17.496641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two types of motor inhibition after action errors in humans

Abstract: Adaptive behavior requires the ability to appropriately react to action errors. Post-error slowing of response times (PES) is one of the most reliable phenomena in cognitive neuroscience. It has been proposed that PES is partially achieved through inhibition of the motor system. However, there is no direct evidence for this link - or indeed, that the motor system is physiologically inhibited after errors altogether. Here, we used transcranial magnetic stimulation and electromyography to measure cortico-spinal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
2
0
0
Order By: Relevance
“…Consequently, measurements of these non-selective effects of inhibitory control on CSE have been used to demonstrate the involvement of the fronto-subthalamic hyper-direct pathway in many different control-demanding scenarios, including those that do not explicitly require action-stopping. For example, unexpected perceptual stimuli (Dutra et al 2018;Tatz et al 2021), action errors (Guan and Wessel 2022), and response conflict (Wessel et al 2019) have all been shown to be followed by shortlatency, non-selective suppression of CSE -in line with prior work showing that all of these events activate the STN (Cavanagh et al 2014;Frank et al 2007;Herz et al 2017;Siegert et al 2014;Wessel et al 2016).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Consequently, measurements of these non-selective effects of inhibitory control on CSE have been used to demonstrate the involvement of the fronto-subthalamic hyper-direct pathway in many different control-demanding scenarios, including those that do not explicitly require action-stopping. For example, unexpected perceptual stimuli (Dutra et al 2018;Tatz et al 2021), action errors (Guan and Wessel 2022), and response conflict (Wessel et al 2019) have all been shown to be followed by shortlatency, non-selective suppression of CSE -in line with prior work showing that all of these events activate the STN (Cavanagh et al 2014;Frank et al 2007;Herz et al 2017;Siegert et al 2014;Wessel et al 2016).…”
Section: Introductionsupporting
confidence: 77%
“…Consequently, measurements of these non-selective effects of inhibitory control on CSE have been used to demonstrate the involvement of the fronto-subthalamic hyper-direct pathway in many different control-demanding scenarios, including those that do not explicitly require action-stopping. For example, unexpected perceptual stimuli (Dutra et al 2018; Tatz et al 2021), action errors (Guan and Wessel 2022), and response conflict (Wessel et al 2019) have all been shown to be followed by short-latency, non-selective suppression of CSE – in line with prior work showing that all of these events activate the STN (Cavanagh et al 2014; Frank et al 2007; Herz et al 2017; Siegert et al 2014; Wessel et al 2016). Finally, the assessment of CSE using TMS and EMG has been a popular and widespread method for studying not only inhibitory control, but also response preparation (Bestmann and Duque 2016; Leocani et al 2000; Raud et al 2020), interhemispheric interactions (Fiori et al 2017; Hamada et al 2014; Hannah and Rothwell 2017), and pathological states that affect the motor system (Badawy et al 2013; Chowdhury et al 2018; Jahanshahi and Rothwell 2017; Smith and Stinear 2016).…”
Section: Introductionsupporting
confidence: 68%